THE USE OF TECHNOLOGIES IN EDUCATION AS RESOURCES TO IMPROVE LEARNING - Zanotto Bonamigo, Greice; Roveda, Mirela (Revista Gênero e Interdisciplinaridade, 2024)
This research aims to analyze the importance of integrating new technologies in education, examining their impact on the transformation of teaching methods and the role of the educator in this digital context. Furthermore, we seek to highlight the new learning paradigms that have emerged with technological advancement and global digitalization, which are reconfiguring the educational structure.